Ventajas y desventajas de tres modelos del servicio de entrega a domicilio en Bogotá comidas rápidas (2017)
The present work demonstrates the importance of home-based service in the establishment of differential links with the client from the approach of the products offered to the place where you want. Likewise, the variables that interfere in the process of implementation of the home service are identified. It includes the three models of delivery to homes. The direct channel model, the intermediary agent channel model and the service channel model per order, as well as the characteristics, actors, delivery processes, advantages and disadvantages of each one.